On the soil fauna of the Antarctic and of the Sub-Antarctic Islands : the Oribatidae <Acari> - Dalenius, Per; Wilson, Ove (Arkiv för Zoologi: Serie 2, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; biologi; leddyr; zoologi

Modchejm : Dva goda v Antarktike. Nauchnaia Norvezhsko-Britansko-Shvedskaia ekspeditsiia 1949-1952 - Giæver, John Schjelderup; Sokolovoj, A V (Gosudarstvennoe Izdat. Geograficheskoi Literatury, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Seismic shooting and related investigations - Robin, Gordon de Quetteville; Hisdal, Vidar (Glaciology III, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; morfologi; seismologi

Temperature, height and humidity - Schumacher, Nils Jörgen; Hisdal, Vidar (Meteorology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; meteorologi

Snow studies at Maudheim - Schytt, Valter; Hisdal, Vidar (Glaciology II, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Snow studies innland - Schytt, Valter; Hisdal, Vidar (Glaciology II, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

The inner structure of the ice shelf at Maudheim as shown by core drilling - Schytt, Valter; Hisdal, Vidar (Glaciology II, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; brehylle; glasiologi; isbrem; isshelf

Ice movement inland - Swithinbank, Charles; Hisdal, Vidar (Glaciology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; snø

The morphology of the inland ice sheet and nunatak areas of western Dronning Maud Land - Swithinbank, Charles; Hisdal, Vidar (Glaciology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; nunataker

The movement of the ice shelf at Maudheim - Swithinbank, Charles; Hisdal, Vidar (Glaciology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; snø

The regime of the ice sheet of western Dronning Maud Land as shown by stake measurements - Swithinbank, Charles; Hisdal, Vidar (Glaciology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; snø

Upper winds over an Antarctic Station - Robin, Gordon de Quetteville (Quarterly Journal of the Royal Meteorological Society, 1957)
Preliminary results from the Norwegian-British-Swedish Antarctic expedition 1949-52. A preliminary note on the upper-air temperatures over Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition 1949-1952, has already been published by Nils Jorgen Schumacher (1955). This note is intended to throw further light on some points raised in Schumacher's paper and to outline the general pattern of upper winds over Maudheim. Owing to the use of a radio theodolite, the data gave a representative picture of the wind structure over an Antarctic station without the excessive bias of previous observations which were limited to periods of clear weather. The detailed report and discussion of aerological observations made at Maudheim will be published shortly by the Norwegian Polar Institute.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; meteorologi

The morphology of the ice shelves of western Dronning Maud Land - Swithinbank, Charles; Hisdal, Vidar (Glaciology I, 1957)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; snø

The regime of the ice shelves at Maudheim as shown by stake measurements - Swithinbank, Charles; Hisdal, Vidar (Glaciology I, 1957)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; snø

Twee jaar in het zuidpool-gebied met de Maudheim-expeditie : de spannende ervaringen van de Noors-Brits-Zweedse expeditie van 1949-1952 naar Antarctis - Giæver, John Schjelderup; Baars, Herman D; Visser, N G; Baars-Jelgersma, Greta (W. de Haan, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Bijela pustinja : dvije godine u Antarktiku : norvesko-britansko-svedska istrazivacka ekspedicija u Antarktiku 1949-1952 - Giæver, John Schjelderup; Mardešić, Petar (Kultura, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Station im Eis : zwei Jahre in der Antarktis : die Norwegisch-Britisch-Schwedische wissenschaftliche Antarktisexpedition 1949-1952 - Giæver, John Schjelderup; Reiher, H (Hermann Haack, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Ice thickness measurements in Queen Maud Land, Antarctica - Robin, Gordon de Quetteville ([Union géodésique et géophysique international. Association international d'hydrologie scientifique], 1956)
Results of seismic soundings.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Basal metabolic rate in the Antarctic - Wilson, Ove (Metabolism: Clinical and Experimental, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldetoleranse; medisin

Snowdrifts around buildings and stores - Roots, Ernest Frederick; Swithinbank, Charles (Polar Record, 1955)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; akkumulasjon; forskningsstasjoner; snø

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Asahi Shimbun Sha, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

Maudheim : deux ans dans l'Antarctique : l'expedition scientifique norvégienne, britannique et suédoise dans l'Antarctique en 1949-1952 - Giæver, John Schjelderup; Poterat, Jacques (Denoël, 1954)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Report on Glaciological Investigations during the Norwegian-British-Swedish Antarctic Expedition - Schytt, Valter (Assemblée Générale de Rome 1954 : Tome IV. Compte-rendus et rapports de la Commission des Neiges et des Glaces, 1954)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Report on glaciological investigations during the Norwegian-Swedish-British Antarctic Expedition, 1949-1952 - Schytt, Valter ([Union géodésique et géophysique international. Association international d'hydrologie scientifique], 1954)
Report of glaciological measurements on ice shelf and ice sheet, Dronning Maud Land.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Some preliminary glaciologial results from Queen Maud Land - Ahlmann, Hans Wilhelmsson (Glacier variations and climatic fluctuations, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; klimaendringer; klimatologi

Med svenskt flyg till Antarktis - Essen, Reinhold von (Ett år i luften : flygets årsbok, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; flyfotografering; luftfoto

Antarktis : norjalais-brittiläis-ruotsalaisen tieteellisen Antarktisretkikunnan vaiheet - Giæver, John Schjelderup; Kilpeläinen, Matti (WSOY, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Sledges of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1953)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; sleder

Trail markers used by the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1953)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; sledehunder

Queen Maud Land Expedition - Robin, Gordon de Quetteville (Marine Observer, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Physiological changes in blood in the Antarctic. A preliminary report - Wilson, Ove (British Medical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskning; fysiologi; medisin; observasjoner

Borgermiddagen på "Bristol" for Maudheim-karene (Norsk polar-tidende, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Den svenska flyggruppen i Antarktisexpeditionen - Essen, Reinhold von (Underrättelser från flygledningen, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfotografering; luftfoto

Erfarenheter från den svenska Antarktisflyggruppen 1951—1952 - Essen, Reinhold von (Teknisk tidskrift, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; flyfotografering; luftfoto

Med svenskt flyg till Antarktis - Essen, Reinhold von (Petroleum, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; flyfotografering; luftfoto

Safir South Pole Survey - Essen, Reinhold von (SAAB Sonics, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; flyfotografering; luftfoto

Some recent work on polar navigation - Foster, L R R (The Journal of The Institute of Navigation, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; navigasjon; polarområdene

Soldage og polarnætter : Norselekspeditionen til Antarktis 1949-1952 - Giæver, John Schjelderup; Windfeld-Hansen, Karina (Grafisk Forlag, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Antarktisboken : med Norsel till Maudheim och Antarktis : den norsk-brittisk-svenska vetenskapliga expeditionen till Antarktis 1949-1952 - Giæver, John; Schytt, Valter (Forum, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Den norsk-brittisk-svenska antarktisexpeditionen 1949-52. Kort översikt av det andra årets arbeten - Liljequist, Gösta H; Schytt, Valter (Ymer, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Fishes collected during the Norwegian-British-Swedish Antarctic expedition 1949-52 - Nybelin, Orvar (1952)
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; fisker; forskning; zoologi

Queen Maud Land. The Scientific Results of the International Expedition - Robin, Gordon de Quetteville (Geographical Magazine, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

The Norwegian-British-Swedish antarctic Expedition 1949-52 - Roots, Ernest Frederick (Science News, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsprogram; geologi; vitenskap

The Maudheim Expedition 1949-52 : part I - Schumacher, Nils Jörgen (Weather, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

The Maudheim Expedition 1949-52 : part II - Schumacher, Nils Jörgen (Weather, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

Med "Norsel" til Dronning Maud Land - Sverdrup, Harald Ulrik (Det norske videnskaps-akademi, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; logistikk

The Norwegian-British-Swedish scientific expedition to Queen Maud land, 1949-52 - Sverdrup, Harald Ulrik (The Antarctic today : a mid-century survey, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The three-nation Antarctic expedition of 1949-52 - Sverdrup, Harald Ulrik (The American Scandinavian review, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Med Norsel til Antarktis - Wilson, Ove (Norges Røde Kors, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; medisin

Sjukvård i Antarktis - Wilson, Ove (Vårt Röda Kors, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; medisin

La spedizione antarctica internazionale 1949-1952 - Zavatti, Silvio (Rivista Marittima, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Den norsk-brittisk-svenska antarktisexpeditionen 1949-52. En översikt av färder och arbeten intill mitten av december - Liljequist, Gösta H (Ymer, 1951)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskningsprogram; vitenskap

Life at Maudheim - Robin, Gordon de Quetteville (Geographical Magazine, 1951)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Utforskning av Dronning Mauds land - Sverdrup, Harald Ulrik (Vi vet, 1951)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Antarctic spotters - Walford, G Brian (Norsk Luftmilitært Tidsskrift, 1951)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; flygning; luftfart

Is the world getting warmer? (The Compass, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Nordmenn i den antarktiske isørken (Nordmanns-forbundet, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Hus på 71 gr. syd - Engh, John; Qvam, Peer (Byggekunst, 1950)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; arkitektur

An international expedition to Antarctica. The Voyage to Queen Maud Land - Roots, Ernest Frederick (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi

Air reconnaissance in Antarctica - Walford, G Brian (ESSO Air World, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flygning; luftfart

Antarctic Austers. Royal Air Force unit's part in the Anglo-Scandinavian Expedition - Walford, G Brian (Flight, 1950)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Antarctica. An Airman's view - Walford, G Brian (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Report by officer commanding R.A.F. Antarctic Flight. Norwegian-British-Swedish Antarctic Expedition, 1949-50 - Walford, G Brian (Air Ministry, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fly; luftfart